2019
DOI: 10.1007/s13399-019-00486-2
|View full text |Cite
|
Sign up to set email alerts
|

Syngas for biorefineries from thermochemical gasification of lignocellulosic fuels and residues—5 years’ experience with an advanced dual fluidized bed gasifier design

Abstract: In many processes proposed for biorefineries, recycling procedures, and industrial or agricultural production processes, residue is generated which could be further transformed by thermochemical conversion via gasification. The technology of dual fluidized bed steam gasification is capable of producing a valuable product gas out of such residue. The generated nitrogen-free product gas can be used for heat and power production and is suitable for separating gases (e.g. hydrogen). However, if the product gas is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 77 publications
7
32
0
Order By: Relevance
“…Gravimetric and GC-FID tar concentrations (on db, at standard temperatu pressure (STP)) are plotted in Figure 11 for gasification temperatures between 654 °C. The trends indicate a significant influence of the gasification temperature on concentration with enhanced tar reforming for increasing gasification temperatur also reported in [19,29,34,35]. By increasing the gasification temperature from 654the gravimetric tar content is reduced significantly from 23-1 g/m³ (db, STP) w GC-FID tars decrease from 18-4 g/m³ (db, STP).…”
Section: Influence Of the Gasification Temperaturesupporting
confidence: 77%
“…Gravimetric and GC-FID tar concentrations (on db, at standard temperatu pressure (STP)) are plotted in Figure 11 for gasification temperatures between 654 °C. The trends indicate a significant influence of the gasification temperature on concentration with enhanced tar reforming for increasing gasification temperatur also reported in [19,29,34,35]. By increasing the gasification temperature from 654the gravimetric tar content is reduced significantly from 23-1 g/m³ (db, STP) w GC-FID tars decrease from 18-4 g/m³ (db, STP).…”
Section: Influence Of the Gasification Temperaturesupporting
confidence: 77%
“…Furthermore, the utilization of residual biomass of lower quality than stem-wood-based biomass is of high interest for improving the economic feasibility of the process as well as increasing the share of renewables in the energy mix. Previous studies have been focused on the use of, e.g., chicken manure, bark, straw, sugar cane bagasse, or exhausted olive pomace as residual biomass [21][22][23]. Different residual biomasses cannot be compared easily since their composition and fuel characteristics vary greatly.…”
Section: Introductionmentioning
confidence: 99%
“…All displayed feed gas compositions are obtained with a new generation 100 kW th DFB gasifier at TU Wien. The DFB process is not elaborated in this study and further information can be found in literature [4,7,8,56,60,61]. The lower part of Table 1 depicts the gas compositions which are derived from the DFB gasification process and are in further consequence used as the feed gas compositions for the methanation process.…”
Section: Resultsmentioning
confidence: 99%
“…Ethylene was found to be the main hydrocarbon in the gasifier product gas besides CH 4 which is not removed by conventional gas cleaning steps like scrubbers or activated carbon filters. Besides ethylene, also hydrocarbons like benzene, toluene, xylene, or naphthalene are often not completely removed [55][56][57]. In this investigation, they are neglected because the concentrations are comparably low.…”
Section: Concept and Methodologymentioning
confidence: 99%